2012
DOI: 10.1111/j.1471-4159.2011.07626.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual REST‐dependence of L1CAM: from gene expression to alternative splicing governed by Nova2 in neural cells

Abstract: J. Neurochem (2012) 120, 699–709. Abstract L1 cell adhesion molecule (L1CAM), an adhesion/signaling protein encoded by a gene target of the transcription repressor RE‐1‐Silencing Transcription factor (REST), is expressed in two alternatively spliced isoforms. The full‐length isoform, typical of low‐REST neural cells, plays key roles in survival/migration, outgrowth/fasciculation/regeneration of axons, synaptic plasticity; the isoform missing two mini‐exons, abundant in a few high‐REST non‐neural cells, maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…However, there have been few studies on splicing in the cancer-derived SH-SY5Y cells (Lannaccone et al 2013;Mikulak et al 2012;Saint Martin et al 2012). In this study, we revealed seven patterns of alternative splicing in the C-transcript by examining the entire length of dystrophin transcript (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…However, there have been few studies on splicing in the cancer-derived SH-SY5Y cells (Lannaccone et al 2013;Mikulak et al 2012;Saint Martin et al 2012). In this study, we revealed seven patterns of alternative splicing in the C-transcript by examining the entire length of dystrophin transcript (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The L1CAM protein exists in two splicing isoforms. In neuronal and cancer cells the splicing factor Nova2 (neurooncological ventral antigen 2) provides for the expression of full-length L1CAM [60]. In all other cells Nova2 expression is repressed by high levels of REST and due to the expression of the splicing factor Nova2 two exons are removed from L1CAM mRNA, namely E2 from the N-terminal and E27 from the C-terminal domains.…”
Section: Regulation Of L1cam Expressionmentioning
confidence: 99%
“…While this protocol has been used routinely to successfully isolate exosomes, in this context it may prove problematic, given L1-CAM gene expression and splicing is known to be regulated by REST. 5 Therefore, it is unclear how perturbed REST expression may alter the levels and forms of L1-CAM expressed on neuronal exosomes. To circumvent this, we elected to measure total peripheral REST in both membrane-bound vesicles and free forms simultaneously in patient plasma, particularly as the latter has yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%